Evidence for nitrogen binding to surface defects for topological insulator Bi2Se3. (1st January 2023) - Gottschalk, Michael; Lee, Mal-Soon; Goodwin, Eric; Mikolas, Camille; Chasapis, Thomas; Chung, Duck Young; Kanatzidis, Mercouri G.; Mahanti, Subhendra D.; Tessmer, Stuart
Abstract: Using scanning tunneling spectroscopy and theoretical simulations we have studied the effects of nitrogen gas exposure on the electronic density of states of Bi2 Se3, a well-studied topological insulator. In carefully controlled measurements, Bi2 Se3 crystals were initially cleaved in a helium gas environment and then exposed to a 22 SCFH flow of ultra-high purity N2 gas. We observe a resulting change in the spectral curves, with the exposure effect saturating after approximately 50 min, ultimately bringing the Dirac point about 50 meV closer to the Fermi level. These results are compared to density functional theory calculations, which support a picture of N2 molecules physisorbing near Se vacancies. Furthermore, ab initio molecular dynamics simulations aided by a Blue Moon ensemble method reveal the dissociative adsorption of N2 molecules which then bind strongly to Se vacancies at the surface. In this scenario, the binding of the N atom to a Se vacancy site removes the surface defect state created by the vacancy and changes the position of the Fermi energy with respect to the Dirac point. Highlights: Scanning tunneling microscopy experiments show evidence of N2 exposure effect on Bi2 Se3 . A shift in the tunneling conductance spectra is observed in real time. Density functional theory calculations provide supporting evidence. Blue moon ensemble method provides a molecular dynamics model.